ETIKA SOSIAL KEMASYARAKATAN DALAM AL-QUR’AN STUDI PEMAKNAAN SURAT AL-HUJURAT DALAM TAFSIR AL-AZHAR - Anshari, Farhan Ahsan (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
The development of the times with technological advances has had a negative impact on moral matters. This article aims to find out the contents of the Al-Qur'an regarding social ethics in QS. Al-Hujurat verses 6-13 in the tafsir al-Azhar by Buya Hamka uses a descriptive-analytic qualitative method with a thematic interpretation approach to explore the meaning of the verses in the social context. The research results of Surat al-Hujurat in Al-Azhar Hamka's interpretation emphasize the importance of maintaining ethics when living in social life, including the prohibition of spreading false news, the order to check news, think about harm and benefits before taking an action, be a fair conflict mediator, respect each other, be open and appreciate differences. Perkembangan zaman dengan kemanjuan teknologi telah membawa dampak negatif pada soal moral. Tulisan ini bertujuan untuk mengetahui isi kandungan Al-Qur’an tentang etika sosial pada QS. Al-Hujurat ayat 6-13 dalam tafsir al-Azhar karya Buya Hamka menggunakan metode kualitatif deskriptif-analitik dengan pendekatan tafsir tematik untuk menggali makna ayat-ayat dalam konteks sosial kemasyarakatan. Hasil Penelitian Surat al-Hujurat dalam tafsir Al-Azhar Hamka menekankan pentingnya menjaga etika ketika hidup bersosial, diantaranya, larangan menyebarkan berita bohong, perintah untuk memeriksa suatu berita, memikirkan madharat dan manfaat sebelum melakukan suatu tindakan, menjadi pendamai konflik yang adil, saling menghormati, bersifat terbuka dan menghargai perbedaan.